Pengaruh Pengungkapan Environmental, Social, and Governance (ESG) Terhadap Profitabilitas - I Komang Bayu Arta Jaya; I Putu Hendra Martadinata (Universitas Pendidikan Ganesha, 2024)
This research was conducted to examine the influence of Environmental, Social, and Governance (ESG) disclosure on the profitability of companies in the oil, gas, and coal mining sectors listed on the Indonesia Stock Exchange from 2018 to 2022. This study employs a quantitative research approach. Secondary data for the research were obtained from the Indonesia Stock Exchange (IDX) website, available at www.idx.co.id, to collect annual report data, and from the official websites of the companies to gather sustainability report data. The sample size for this study comprises 159 companies, selected through purposive sampling method. The findings of this research indicate that (1) environmental disclosure has a significant negative effect on company profitability, (2) social disclosure has a significant positive effect on company profitability, and (3) governance disclosure has a positive but nonsignificant effect on company profitability.